Electrocoagulation of phenol for wastewater treatment - A-Mohammed, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Electrocoagulation is an electrochemical process of treating polluted water where sacrificial anode corrodes to produce active coagulant (usually aluminum or iron cations) into solution. Accompanying electrolytic reactions evolve gas (usually as hydrogen bubbles). The present study investigates the removal of phenol from water by this method. A glass tank with 1 liter volume and two electrodes were used to perform the experiments. The electrode connected to a D.C. power supply. The effect of various factors on the removal of phenol (initial phenol concentration, electrode size, electrodes gab, current density, pH and treatment time) were studied. The results indicated that the removal efficiency decreased as initial phenol concentration increased, the highest removal obtained at pH in the range (6-8), the removal enhanced with increasing electrode size and decreasing the gab between the electrodes. The optimum current density obtained at 221 A/m2.